(untitled) (The Pakistan Development Review, 1994)
Cold war US-Soviet relations were characterised by a large gap between hostile talk and cautious action, though both countries backed and armed rival sides in wars in the third world. During the cold war US foreign policy was detennined by the sole objective of containing Soviet territorial and ideological ’expansionism’. This was also the defining element in US-Indian subcontinent relations in the coldwar period. Thus the main reason for the estrangement in US-India relations is not hard to discern-while the US aggressively sought partners in its anti-Soviet alliance system, India nurtured its economic and military supplies relationship with the Soviet Union. Furthermore, while there persisted a fundamental conflict between Pakistan and India over the Kashmir issue, Pakistan participated in the US sponsored anti-Soviet alliance system and gained from US military and economic assistance.